Grafting methods and time in pomegranate (Punica granatum) under semi-arid agro-climatic condition of Maharashtra - CHANDRA, RAM; JADHAV, V T (The Indian Journal of Agricultural Sciences, 2014)
The experiment was conducted during 2007–08 and 2008–09 to standardize grafting methods and time in pomegranate. The scion sprouting was highest (96.67%) when wedge grafting done on 30 January at 21 days after grafting (DAG). Maximum graft success (85.83%) was recorded at 90 DAG with wedge grafting done on 30 January. The growth performance of wedge grafted plants was better with 15 December grafting. In general, the wedge grafted plants had better scion-rootstock compatibility than tongue grafting. Wedge grafting done on 30 January produced more shoot and root biomass owing to its better shoot and root development.